Leadership Behaviours for Next Generation Supply Chains - Securing the success of strategic supply chain initiatives today and for tomorrow (interim research report) - Wilding, Richard; Waller, Alan; Habib, Farooq; Wheatley, Malcolm (Cranfield University, 2018)
Interim research report by the Efeso Consulting and Cranfield School of Management partnership.The report is an interim summary of the findings from the 'Leadership Behaviours for next Generation Supply Chains' research programme. It delineates the principal survey findings, describes the conceptual Supply Chain Leadership framework, and sets the scene for the programme of interviews and workshops that is now underway.
Keywords: 'supply chains'; 'leadership tendencies'; 'Change Models'; 'behavior change pattern'; 'Performance management and measurement'; 'Logistics and Supply Chain Management'